Deformation Failure and Support Test of Surrounding Rock in Deep Arched Roadway with Straight Wall - Shuqi Pan; Shuaitao Liu; Liming Cao; Jianqiang Guo; Chao Yuan (Advances in Civil Engineering)
The deformation and failure of the uphill roadway on the 3rd horizontal track in the No. 6 Mine of Pingdingshan Coal Group was taken as the engineering background. The similar simulation material of the roadway surrounding rock with quartz sand as the aggregate, cement as the cementing agent, and gypsum powder as the regulator was selected. Through mechanical tests on 25 sets of specimens with different proportions, the best proportion of similar simulated materials for simulating the deformation and failure of the surrounding rock of the roadway was obtained. Later, a large-scale deep mine roadway simulation test system independently developed by the company was used to carry out the roadway deformation and failure test. First, load the test body to the set initial stress state, and then carry out the full-face excavation and unloading of the roadway; finally, load it in the vertical direction until the roadway wall is damaged. It can realize the actual effect of simulation of roadway deformation and failure under the path of “high stress + internal unloading + stress adjustment.” The results showed that after the deep roadway is excavated with preload and high stress, the surrounding rock deformation, failure, and instability of the roadway mainly experience 3 periods: the first period is the period of uniform deformation of the roadway surrounding rock, the second period is the development period of the roadway surrounding rock slab structure, and the third period is the period of instability of the roadway surrounding rock slab structure. Combined with the time period of deformation and failure of the surrounding rock of the roadway, the damage scope of the surrounding rock and the actual situation of the site engineering. A step-by-step combined roadway repair and support plan of “bolt mesh + shotcrete + full-face hollow grouting anchor cable” with hollow grouting anchor cable as the core was determined. The stability of the repaired roadway has been significantly improved, ensuring the long-term use of the roadway.